2014
DOI: 10.15376/biores.9.3.4946-4957
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Esters Formation during Cellulose Liquefaction in Sub- and Supercritical Ethanol

Abstract: Cornstalk cellulose was liquefied in sub-and supercritical ethanol using an autoclave at 320 °C with 160 mL of ethanol. The effects of reaction time on esters formation during cellulose liquefaction were investigated. The yield of esters was 10.0% at 30 min, increasing to 19.1% after 60 min. Ethanol favored esters formation from cellulose liquefaction. The liquid products at different reaction time were analyzed by FT-IR and GC/MS. The results showed that many free radicals were produced in sub-/supercritical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In recent years, significant progress has been made in the preparation of levulinic acid and its esters by catalytic liquefaction of woody fiber biomass. In this experiment, by analyzing the liquid products of glucose, cellobiose and cellulose, we found that in the process of preparing ethyl levulinate by acid catalytic liquefaction of lignocellulosic biomass in ethanol, ethyl levulinate mainly came from cellulose liquefaction. Moreover, we found that ethyl levulinate can be generated not only by glucose, fructose, 1,6-anhydro-beta- d -glucopyranose (AGP), levoglucosenone (LGO), and 5-HMF as reported in previous studies , (as shown in Figure S10), but also by the other pathways shown in Figure .…”
Section: Resultssupporting
confidence: 73%
“…In recent years, significant progress has been made in the preparation of levulinic acid and its esters by catalytic liquefaction of woody fiber biomass. In this experiment, by analyzing the liquid products of glucose, cellobiose and cellulose, we found that in the process of preparing ethyl levulinate by acid catalytic liquefaction of lignocellulosic biomass in ethanol, ethyl levulinate mainly came from cellulose liquefaction. Moreover, we found that ethyl levulinate can be generated not only by glucose, fructose, 1,6-anhydro-beta- d -glucopyranose (AGP), levoglucosenone (LGO), and 5-HMF as reported in previous studies , (as shown in Figure S10), but also by the other pathways shown in Figure .…”
Section: Resultssupporting
confidence: 73%
“…Recently, alcohols have been utilized as an alternative solvent in the liquefaction of various types of biomass, including cellulose, lignin, sewage sludge, and microalgae, due to their advantages with better solubility of organic intermediates, hydrogen donor properties, and easier separation due to their low boiling points [50][51][52][53][54][55][56][57][58][59]. Compared to water, alcohols such as methanol and ethanol have much lower critical temperatures and pressures.…”
Section: Mesoporous Silicate Materials Containing Zirconium Have Highmentioning
confidence: 99%
“…Table 1 shows that ketones (Carbon numbers C 5 ∼C 20 ), esters (Carbon numbers C 7 ∼C 30 ), alkanes (Carbon numbers C 10 ∼C 30 ) have a higher content in BO, and alcohols, acids, aldehydes and phenols were lower. Acetates and methyl esters were the dominant compounds of esters, this indicated that CH 3 • and CH 3 C = O• radicals were produced from supercritical acetone, the addition and condensation among these methyl and acetyl radicals and cellulose active fragments produced a lot of esters, on the other hand, the esterification between acids and alcohols also have a contribution on esters formation (34). Ketones were composed of aliphatic ketones (4-Hydroxy-4-methyl-2pentanone, etc.…”
Section: Gc-ms Analysis For Bo Obtained From Various Acetone Dosagesmentioning
confidence: 97%
“…According to 3.5.1 and 3.5.2(above), the formation pathways and networks of dominant chemicals (ketones, esters, acids, alcohols, alkanes, aldehydes, glucosides, etc.) during cellulose liquefaction in supercritical acetone were developed (21,29,34,37,38). It is shown in Figure 8.…”
Section: Chemicals Distribution In Bo and The Formation Pathwaysmentioning
confidence: 99%